ATH434 Reduces α‐Synuclein‐Related Neurodegeneration in a Murine Model of Multiple System Atrophy. Issue 11 (8th July 2021) - Heras‐Garvin, Antonio; Refolo, Violetta; Schmidt, Claudio; Malfertheiner, Katja; Wenning, Gregor K.; Bradbury, Margaret; Stamler, David; Stefanova, Nadia
ABSTRACT: Background: Multiple system atrophy (MSA) is a fatal neurodegenerative disorder characterized by aggregated α‐synuclein (α‐syn) in oligodendrocytes and accompanied by striatonigral and olivopontocerebellar degeneration and motor symptoms. Key features of MSA are replicated in the PLP‐α‐syn transgenic mouse, including progressive striatonigral degeneration and motor deterioration. There are currently no approved treatments for MSA. ATH434 is a novel, orally bioavailable brain penetrant small molecule inhibitor of α‐syn aggregation. Objectives: To characterize ATH434 for disease modification in a mouse model of MSA. Methods: Six‐month‐old PLP‐α‐syn mice (MSA mice) were ATH434‐treated (ATH434 in food) or untreated (normal food) for 6 months. Motor behavior and numbers of nigral and striatal neurons were evaluated. α‐syn aggregates and oligomers were quantified by immunohistochemical and western blot analyses. Microglial activation and neuroinflammation were assessed by histological and molecular analyses. Ferric iron in the Substantia nigra was evaluated with the Perls method. Results: ATH434‐treated mice demonstrated preservation of motor performance in MSA mice that was associated with neuroprotection of nigral and striatal neurons. The rescue of the phenotype correlated with the reduction of α‐syn inclusions and oligomers in animals receiving ATH434. ATH434‐treated mice exhibited significantly increased lysosomal activity of microglia without increased pro‐inflammatory markers, suggesting a role in α‐syn clearing. ATH434‐treatment was associated with lower intracellular nigral iron levels. Conclusions: Our findings demonstrate the beneficial disease‐modifying effect of ATH434 in oligodendroglial α‐synucleinopathy on both the motor phenotype and neurodegenerative pathology in the PLP‐α‐syn transgenic mouse and support the development of ATH434 for MSA. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society